The Influence of Student Organizational Activeness on Learning Achievement of Civil Engineering UNJ Students - Dhea Islamiyanti Oktora; Rosmawita Dewi Saleh; M. Agphin Ramadhan (CIVED, 2020)
This study aims to find out: (1) The activeness of UNJ Civil Engineering students in following organizations; (2) Learning achievement of the UNJ Civil Engineering students who participated in organization; (3) The influence of student organizational activeness on learning achievement of UNJ Civil Engineering students. This study used quantitative method. The population in this study were active students of the S1 Engineering Education of Building and D3 Civil Engineering class of 2017-2019 who participated in organizations in the UNJ environment by taking samples using the proportionate stratified random sampling technique. The results of this study are: (1) Civil Engineering Students of UNJ who join the organization are classified as very active with percentage of 63,64%; (2) Civil Engineering students of UNJ who participate in the organization have very satisfying learning achievement with percentage of 68,60%; (3) There is no influence between the activeness of the organization on the learning achievement of UNJ Civil Engineering students with a significant level of 0,504 > 0,05 and t-count of -0,670 < t-table of 1,980.